High‐resolution mapping of Manawatu palaeochannels. (6th April 2018) - Lo Re, Giulia; Fuller, Ian C.; Sofia, Giulia; Tarolli, Paolo
Abstract : New remote sensing techniques, such as airborne laser scanning (LiDAR), have led to a dramatic increase in terrain information, providing new opportunities for landform analysis. A major advance in using LiDAR‐derived high‐resolution topography (HRT) is the capability to provide an accurate and detailed terrain morphology. This study aims to use LiDAR HRT to identify palaeochannels of the Manawatu River (New Zealand) using an automated procedure based on the statistical analysis of landform curvature. The approach can provide rapid assessment and classification of floodplain topography. The proposed analysis is crucial, especially for intensively used floodplains requiring effective flood management and mitigation.